(untitled) (African Journal of Biomedical Research, 2020)
Parental knowledge of antibiotic use in upper respiratory tract infections (URTI) impacts significantly in the preservation of antibiotic efficacy, yet has not been adequately studied in Nigerian settings. This present study evaluated the knowledge, attitudes and self-medicating practices of caregivers towards the use of antibiotics in URTI among children. The study was a cross-sectional and prospective survey. Parents visiting two hospitals (Nsukka General Hospital - rural and Enugu State University of Technology Teaching Hospital- urban) with their sick children (12 years and under) were approached to complete a 24-item questionnaire. The items assessed parental knowledge of, attitudes and self-medicating practices towards antibiotics in cases of URTI. Frequencies, means and inferential multivariate (chi-square, t-tests and regression) data analysis were conducted. The parents exhibited poor knowledge in most of the knowledge items. Younger parents, those visiting the urban hospital and those with higher educational status exhibited significantly better knowledge of antibiotics and URTI (p<0.05). The parents indicated marginally accepting attitudes towards antibiotics use and misuse and this was influenced largely by better antibiotic knowledge and better educational qualifications (p<0.001). However parents from both hospitals frequently self-medicated (88.6%) and acknowledged poor practices towards antibiotics such as the use of left over antibiotics. Majority (85%) of the parents also said they received antibiotics after they demanded it from their physicians. Parents in these study settings in Nigeria, possessed poor knowledge and positive attitudes of antibiotic use in their children, and exhibited poor practices when utilizing them